Asset transfer programme for the ultra poor: A randomized control trial evaluation - Bandiera, Oriana; Burgess, Robin; Das, Narayan C; Gulesci, Selim; Rasul, Imran; Shams, Raniya; Sulaiman, Munshi (BRAC Research and Evaluation Division, 2022)
The world’s poorest people lack both capital and skills and are trapped in low return occupations. However, whether their economic lives can be transformed by programs which attempt to tackle both constraints by providing assets and training to enable them to run small businesses is unknown. To shed light on this issue we conduct a randomized evaluation of an entrepreneurship program that provides assets and training to the poorest women in rural Bangladesh. We find that the program transforms the occupational choices of the poor women who participated in the program by inducing them to spend more time in self-employment, less in wage labour and increases their labour market participation, leading to a 36% increase in annual income on average. Moreover, the program leads to an increase in wages at the village level and its effects spill over to other poor women who experience an increase in labour supply and income.